PENGARUH PENGGUNAAN STRATEGI GUIDED DISCOVERY LEARNING TERHADAP PRESTASI BELAJAR PESERTA DIDIK - Novita, Fani; Setyaningrum, Saumi; Hasmy, Ali (Jurnal As Sibyan, 2024)
This study aims to observe the effect of using the Guided Discovery Learning strategy on student learning achievement in animal classification material in class V MIN 2 Pontianak in the 2022/2023 school year. The research method used was quasi experiment with the population of all grade V students, where the sample consisted of two classes, namely class V A as the experimental class and class V D as the control class. Data were collected through t-test, and the results showed that the learning achievement of students taught with the Guided Discovery Learning method had a value of 74.00 (high category), while students who did not use the method had a value of 71.01 (high category). The difference in learning achievement between the two groups was 2.99, and the effect of using the Guided Discovery Learning method on student learning achievement was 10.4%. Thus, it can be concluded that the use of the Guided Discovery Learning learning strategy has a positive impact on student learning achievement in animal classification material in class V of MIN 2 Pontianak in the 2022/2023 academic year